2011
DOI: 10.1143/jjap.50.04da02
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Approach for Enhancement of n-Channel Metal–Oxide–Semiconductor Field-Effect Transistor Performance with Carbon-Doped Source/Drain Formed by Molecular Carbon Ion Implantation and Laser Annealing

Abstract: Enhancement of n-channel metal–oxide–semiconductor field-effect transistor (nMOSFET) performance with a carbon-doped source/drain (Si:C-S/D) was approached analytically for the first time. Si:C-S/D was formed by molecular carbon (C7H x ) ion implantation and laser annealing. C7H x implantation forms a smooth interface between Si:C layers and Si substrates, and laser annealing also achieves a high carbon concentration of substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Si:C-S/D is one of the most attractive booster items for nFET, and the method of the Si:C-S/D formation using a combination of molecular carbon ion (C 7 H x ) implantation and non-melt LA has been investigated [1][2]. Figure 2 shows the process flow of Si:C-S/D using the SPE technique.…”
Section: Analytical Approach For Strained Si:c-s/d Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Si:C-S/D is one of the most attractive booster items for nFET, and the method of the Si:C-S/D formation using a combination of molecular carbon ion (C 7 H x ) implantation and non-melt LA has been investigated [1][2]. Figure 2 shows the process flow of Si:C-S/D using the SPE technique.…”
Section: Analytical Approach For Strained Si:c-s/d Formationmentioning
confidence: 99%
“…Then, LA is conducted for SPE and the activation of Si:C-S/D. In order to effectively develop Si:C-S/D, a measurement of the channel stress by UV Raman spectroscopy using a particular test pattern was established [2]. Figure 3 shows the structure of the test pattern and the resultant Raman peak shift at channel regions with Si:C-S/D using two C 7 H x -implantaion conditions.…”
Section: Analytical Approach For Strained Si:c-s/d Formationmentioning
confidence: 99%
“…In our previous work, we reported that high stress Si:C-S/D with high carbon concentration of substitution (C Si:C ) formed by molecular carbon ion (C 7 H x ) implantation and solid-phase epitaxy (SPE) using non-melt laser annealing (LA) produces the large channel strain. It was also found that the combination of rapid thermal annealing (RTA) and LA in order to reduce the parasitic resistance of transistors relaxes the strain in Si:C layers [4]. The retrograde C profile with low temperature SPE has been also proposed as a countermeasure [5].…”
Section: Introductionmentioning
confidence: 99%
“…Various RTA conditions before LA at 1200 °C were examined for SPE and activation. The stress at the channel region was measured by UV Raman spectroscopy using the particular Raman-test pattern [4]. The measurement of R s in Si:C layers was performed by four-point probe (4PP) method.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we propose the generation mechanism of channel-stress. Figure 1 shows the test structure [3]. The stress at the channel region was measured by UV Raman spectroscopy using these structures.…”
Section: Introductionmentioning
confidence: 99%